Teachers' Views on the Roles of Instructional Media in Teaching Large Classes in Selected Secondary Schools in Ilorin South Local Government, Ilorin. - Mosiforeba, V. A.; Michael , A. F. (International Journal of Educational Management, 2022)
This research was aimed at investigating the views of teachers of Secondary Schools in Ilorin South Local Government Area Ilorin on the roles of instructional media in teaching large classes. Areas explored included the roles of instructional media in large classes with regards to class management, teaching and learning and evaluation of students' academic progress. The sample used for the study included 150 teachers who responded to a questionnaire used to elicit information on their views on the topic. Using frequency counts and percentages for analysis, it could be inferred that instructional media could be used to manage large classes and monitor students' academic progress in large classes. However, teachers could not agree on whether instructional media directly help students' academic progress. For effective large classroom management and monitoring of students' academic progress, it was recommended that instructional media (such as computers, public address system, etc.) should be made available to teachers.